Gestión administrativa-financiera y de servicio y su incidencia en la rentabilidad del complejo Manila Park Center, periodo 2013, Manual de procedimiento. - Pacheco Intriago, Karen Narcisa (2014)
This research justifies its practical and functional at the local , regional and why not say nationwide, since the results obtained will contribute to the development oCOMPLEJO PARK CENTER MANILA and for those complexes that are the sameproblems , considering an immediate solution model performing propeAdministrative Management - Financial and Service, to promote efficiency andeffectiveness in carrying out its operations by providing a reasonable degree osecurity , increasing revenues , reducing costs and simplifying their tasks througha process reengineering for meeting the goals and objectives set in the short,medium and long term , and to appraise their competitive weaknesses , establishpotential risks they face financial management and service defined in a broadesense as a process effected , reliability of financial reporting and strengthenconfidence in compliance with the laws and regulations that apply. The scientific theory is based with the development of the theoretical mark infunction of each variable of the hypotheses; they are defined basic concepts onthe Gestión Administrative, Financial and of Service that you/they offer the TouristComplexes. It fits to highlight that for the realization of the investigation it was used thefollowing methods; the descriptive one that allowed to observe the existent realityin the products and services that he/she offers the Tourist Complex Manila Park.........................................................